ANALISIS DISIPLIN KERJA PEGAWAI NEGERI SIPIL (Studi Pada Bagian Sumber Daya Alam Sekretariat Kabupaten Kutai Timur) - Dahliana, Dahliana (PREDIKSI, 2016)
This study aims to determine to what degree Work Discipline of Civil Servants Under Section Natural Resources Secretariat of the East Kutai Regency. This study used a qualitative descriptive approach which seeks to describe a phenomenon studied, namely employee discipline.The results showed showed that the general level of employee discipline on the part of the Natural Resources Secretariat of the East Kutai Regency is 73.7% and is included in the interval 56% - 75% or fall into the category quite well. Based on the analysis, it can be concluded that the Work Discipline of Civil Servants (PNS) in the Department of Natural Resources Secretariat of the East Kutai Regency in the category quite well, this means that the writer formulated hypotheses in this study can be received and verified.-style: normal'>Â Â